Decoding the Post-Analysis Stage in Design Process: Proposing a Framework of Form Synthesis Strategies - Babiker, Mohammed Gismallah Elkhider (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
Despite the diversity of methodologies and approaches in architectural design process, there are a shared agreement on the inevitable existence of the stages "analysis" and "synthesis" as norms sequences during the process. Synthesis is looking for an invention of embodiment to the data from analysis, and generating design ideas. Surprisingly, this stage is remained with a very scare studies and least discussions, although it is "the most crucial and most difficult aspect of designing, and indeed the most intimidating to a fledgling designer". Leaving the stage to the free well of designer intuition and personal creativity. This tendency has engendered two conflicts, firstly the intuitive creativity is unreliable and far from satisfy the elementary demand of methodical approach. Secondly, the freedom margin turns to a place of incompetence and confusion leads to random actions to synthesize the intended form, which put the product under the suspicions. Decoding the post analysis stage becomes an argent appeal, thus the main aim drawn for this research is to synthesis an explanatory framework exhibits set of shared and accepted form synthesis strategies, to become as normative map for designers that can broaden their conceptual capacity and inform their decisions during the post analysis stage in design process. Creating such inclusive framework acquired to unify all the form design theories in one plateau and connected them by appointing a formulation criteria dissolving the theories to their basic design ingredients. The Logical argumentation research method basic condition tends to pick a group of previously unappreciated disparate factors, then reconnected them to reveal a unified framework. The literature survey on the area of descriptive form design theories that take the mold of framework, revealed a 45 form design theory distributed in 9 different frameworks. The classifying of the previous findings established among the different texts, resulted 34 form design theories, 4 among them were addressed in the same name by different authors, while the other 30 showed differences on terms and descriptions. Correlating the fragmented theories together by affiliating the conceptual descriptions obtained by them, enclose the 34 form design theory into 9 inclusive form design theories. After the relabeling process the result are: Theory of Deep Structure Transformations, Theory of Layering Meaning, Theory of Deformation, Theory of Form Performance, Theory of Information, Theory of Metaphor as Generator, Theory of Pattern Language, Theory of Transformation of Specific Type, and Theory of Space as Generator. The design theories dissolved by an analytical device developed from Salama's Design Ingredients Theory. The result unfolded the design ingredients for each Form design theory as Strategy, Technique and Tool. Finally, the proposed framework was synthesized and presented in a diagrammatic organization, exhibited verified and accepted theories among the authors, thus they can reach the extent of being norms for form synthesis. The framework holds of the ability to provide a conceptual clarity via offering multiple start points, which broadening Designer's conceptual capacity to answer the demands subjected from the variety of design tasks. Not to forget the reason of adoption that attached to each strategy allows Designer to place himself exactly in the right selection to tackle the task. Keywords: Form synthesis process; Form generation process; Design methods; Design theories.

ÖZ:Mimari tasarım sürecinde metodolojilerin ve yaklaşımların çeşitliliğine rağmen, süreç boyunca norm dizileri olarak "analiz" ve "sentez" aşamalarının kaçınılmaz varlığı konusunda ortak bir mutabakat vardır. Sentez, analiz verilerinden somutlastirmaya yönelik bir icat ve tasarim fikirleri üretme cabasindadir. Şaşırtıcı bir şekilde, bu aşama çok korkutucu çalışmalar ve en az tartışmalarla kalırken, "tasarımın en önemli ve en zoru parcasi olan ve ayni zamanda ilk olarak, yeni başlayacak bir tasarımci icin en korkutucu yön". Sahneyi, tasarımcınin sezgilerine ve kişisel yaratıcılığına bırakmak. Bu eğilim iki anlasmazlik ortaya çıkardı, ilk olarak, sezgisel yaratıcılıgin güvenilmez olmasi ve metodik yaklaşımın temel talebini tatmin etmekten uzak olmasi. İkincisi, özgürlük marjı yetersizlik olmaya dönüşüyor ve karışıklık, ürünün kuşkuya düştüğü şekli sentezlemek için rasgele eylemlere yol açar. Son analiz aşamasının kodunun çözülmesi argenti bir itiraz haline gelir, bu nedenle bu araştırma için çizilen asıl amaç, tasarımcıların kavramsal kapasitelerini genişletebilecekleri normatif harita haline gelmek için ortak ve kabul edilmiş form sentez stratejileri seti sergileyen açıklayıcı bir çerçeveyi sentezlemektir. Tasarım sürecinde son analiz aşamasında alınan kararlar. Yazılı analiz aşamasının çözülmesi argüman çağrısı haline gelmektedir, bu nedenle bu araştırmanın ana amacı, tasarım aşamasında analiz sonrası aşamada kavramsal kapasitelerini genişletip kararlarını açıklayabilecek, tasarımcılar için normatif harita haline gelmek için açık ve paylaşılmış form sentez stratejileri seti sergileyen açıklayıcı bir çerçeveyi sentezlemektir. Tüm form tasarım teorilerini bir platoda birleştirecek şekilde kapsayan, bu kapsayıcı çerçeveyi oluşturmak ve teorileri temel tasarım bileşenlerine eriten bir formülasyon kriteri atayarak bunları birbirine bağlamak. Mantıksal argümantasyon araştırma yönteminin temel şartı, daha önce kabul edilmeyen farklı faktörlerden oluşan bir grup seçme eğilimi gösterir, sonra birleşmiş bir çerçeve ortaya çıkarmak için onları yeniden kurmaktir. Çerçeve kalıp olan tanimlayici form tasarım teorileri alanıyla ilgili literatür araştırması, 9 farklı ana baslik içinde dağıtılan 45 form tasarım teorisini ortaya koymuştur. Farklı metinler arasında kurulan daha önceki bulguların sınıflandırılması, 34 form tasarım kuramı ile sonuçlandı; bunların 4 tanesi farkli yazarlar tarafindan aynı isim ile sonuclandirilirken, diğer 30 tanesi terim ve tanımlarda farklılıklar gösterdi. Parçalanmış teorileri, kendilerince elde edilen kavramsal tanımlamaları birleştirerek birbiriyle ilişkilendirerek 34 form tasarım teorisini, 9lu kapsayan form tasarım teorisine dahil edildi. Yeniden isimlendirmeden sonra sonuç: Ic Form Dönüşümleri Teorisi, Katman Anlam Teorisi, Deformasyon Teorisi, Bicim Performans Teorisi, Bilgi Teorisi, Uretken gibi Olarak Metafor Teorisi, Kalip Dili Teorisi, Spesifik Model Dönüşüm Teorisi, Ve Uretken Olarak Uzay Teorisi. Tasarım teorileri, Salama'nın Tasarım Malzemeleri Teorisi'nden geliştirilen analitik bir arac ile çözülmüştür. Sonuç olarak, her Bicim tasarıminin teorisi tasarım unsurlarını Strateji, Teknik ve Araç olarak ortaya çıkardı. Son olarak, önerilen diyagram sentezlenip diyagramatik bir organizasyonda icerisinde sunuldu, yazarlar arasında doğrulanmış ve kabul edilmiş olan bu teoriler sergilendi, bu sayede form sentezi için norm olma boyutuna ulaşilabildi. Olusturulan diyagram, tasarımcıların çeşitli tasarım görevlerinden kaynaklanan taleplerini karşılama konsept kapasitesini genişleten çoklu başlangıç noktaları sunarak, tasarimcilarin kavramsal bir netlik sağlama yeteneğine sahip olmalarina yardimci olmaktadir. Her stratejiye eklenen uyumun sebebi unutulmamalidirki, tasarimci nin görevi üstlenmek için tam olarak doğru seçim yapmasina katki sağlar. Anahtar kelimeler: Bicim sentezleme süreci; Bicim oluşturma süreci; Tasarım
Master of Science in Architecture. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2018. Supervisor: Assist. Prof. Dr. Badiossadat Hassanpour.
Keywords: Architecture; Architectural Design; Form synthesis process; Form generation process; Design methods; Design theories